Analysis of Bad Credit at PT. State Savings Bank (BTN) - David Gibson Nababan; Vetric Styven Silaban; Bunga Meylani Br Surbakti; Selvina Audina Nasution; Sabda Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bad credit (non-performing loans) at Bank BTN is a reason for investment decisions for the public and investors. By knowing bad credit in a company, it provides clearer information for making investments. This research was conducted to provide information about bad credit at BTN bank, which is one of the most trusted banks in Indonesia. It is hoped that this research will help the public increase their competency in how to invest through the value of bad credit or non-performing loans. This research aims to analyze the influence of bad credit on investment decisions at BTN bank. The research method used is a qualitative research method using Bank BTN financial report data regarding bad loans or non-performing loans from 2007 to 2022. This research suggests that investment decisions at Bank BTN can be based on the value of net bad loans which are still safe.